Determination of Parents Burnout for Child with Type 1 Diabetes Mellitus in Endocrine and Diabetes Center at Al-Nasiriyah City - Amer Muhasin Naser (Journal of Global Pharma Technology, 2016)
Objectives: To assess level of parents’ burnout   for child with type 1 diabetes mellitus (T1DM). Also to find out the association between parents burnout, and demographic characteristics (child age at diagnosis, gender of parents’, parents' level of education).Methodology: A descriptive cross-sectional study design was conducted in Endocrine and Diabetes Center at AL-Nasiriyah city to assess level of parents' burnout for child with T1DM and find out the association between parents burnout, and demographic characteristics (child  age at diagnosis ,gender of parents' , parents' level of education). The study was conducted on 200 parents' who have child with type T1DM. The data were collected using the interview and the questionnaire form, which was designed to contain (44) items containing the form of personal and demographic characteristics and parents'' burnout, as followed by Maslach burnout interview after modification (Maslach, 2001). This part involves (34) distributed into three sub-domains, which are (Emotional exhaustion, Personal accomplishment and Depersonalization). The data were analyzed using descriptive statistics method (frequency, percentages, Chi Square). Results: The study shows that the parents' are moderately burned out and there is no statistically significance between parents' bournut and parents' demographic characteristics. Recommendations: Study recommended establishing educational program should be done for parents' to decreases burnout level. Instructional class or folder given for parent's for increase their knowledge toward effects of burnout on their daily physical and emotional functionsKeywords: Parents', Burnout, T1DM.